PERAN PEJABAT PEMBUAT AKTA TANAH DALAM MENDUKUNG IMPLEMENTASI TRANSFORMASI DIGITAL LAYANAN PERTANAHAN TERKAIT SERTIPIKAT ELEKTRONIK - Nurul Farahzita; Fransiscus Xaverius Arsin (The Juris, 2022)
The issuance of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency (ATR/BPN) Number 1 of 2021 concerning Electronic Certificates as a form of digital transformation of land services resulted in changes in the pattern of land services carried out by Land Deed Making Officials (PPAT) as public officials. in the land sector. With these changes, a PPAT is required to be able to develop and master the procedures for digital land services, this also poses several obstacles in its implementation. This study aims to make a PPAT know the role and procedures for digital land services to support its performance and be able to overcome problems that arise in the field of electronic services. This study uses a qualitative method with an analytical descriptive approach with data obtained through observation, documentation and interviews with sources. The results of this study indicate that PPAT has a role in implementing the digital transformation of land services in terms of educating the public about legal actions on certified land, using biometric record technology in verifying people, preventing embezzlement or identity falsification, ensuring the suitability of certificates with information from Database and ensure the suitability of the subject of rights and the parties in the deed.